Endothelial microparticles act as novel diagnostic and therapeutic biomarkers of circulatory hypoxia‐related diseases: a literature review. Issue 9 (18th March 2017) - Deng, Fan; Wang, Shuang; Zhang, Liangqing
Abstract: Circulatory hypoxia‐related diseases (CHRDs), including acute coronary syndromes, stroke and organ transplantation, attract increased attention due to high morbidity and mortality. Mounting evidence shows that hypoxia‐induced oxidative stress, coagulation, inflammation and angiogenesis play extremely important roles in the physiological and pathological processes of CHRD‐related vascular endothelial injury. Interestingly, hypoxia, even hypoxia‐induced oxidative stress, coagulation and inflammation can all induce release of endothelial microparticles (EMPs). EMPs, shed from activated or apoptotic endothelial cells (ECs), reflect the degree of EC damage, and elevated EMP levels are found in several CHRDs. Furthermore, EMPs, which play an important role in cell‐to‐cell communication and function, have confirmed pro‐coagulant, proinflammatory, angiogenic and other functions, affecting pathological processes. These findings suggest that EMPs and CHRDs have a very close relationship, and EMPs may help to identify CHRD phenotypes and stratify the severity of disease, to improve risk stratification for developing CHRDs, to better define prophylactic strategies and to ameliorate prognostic characterization of patients with CHRDs. This review summarizes the known and potential roles of EMPs in the diagnosis, staging, treatment and clinical prognosis of CHRDs.